Regulatory Reform and Policy Mapping in Indonesia’s Traditional Medicine, Health Supplement, and Cosmetic Sectors - Mohamad Kashuri; Arry Yanuar (Borneo Journal of Pharmacy, 2025)
This study systematically analyzed Indonesia's regulatory reforms for traditional medicines, health supplements, and cosmetics (TMHSC) issued between 2020 and 2024. The objective was to map the scope, distribution, and policy orientation of the 35 regulations enacted by the Indonesian Food and Drug Authority (BPOM) within the framework of the National Medium-Term Development Plan (RPJMN 2020–2024). A qualitative policy analysis was employed, combining document analysis, thematic coding, and comparative benchmarking with frameworks from the ASEAN, European Union (EU), and Organisation for Economic Co-operation and Development (OECD). The findings show that 25 regulations were directed toward strengthening regulatory services, nine targeted compliance and Good Manufacturing Practices (GMP), and one supported research and innovation through preclinical testing standards. This distribution reflects a policy trajectory that prioritizes service delivery and compliance assurance, while progressively integrating evidence-based approaches to research and innovation. A comparative analysis revealed a strong alignment with ASEAN harmonization initiatives and an incremental adoption of international benchmarks, such as ISO 22716 for cosmetics and the WHO GMP guidelines for herbal medicines. Overall, Indonesia's TMHSC regulatory transformation demonstrates a balanced and adaptive governance model that safeguards public health, promotes innovation, and enhances regional policy coherence. The results provide practical implications for policymakers, particularly BPOM and ASEAN member states, in developing regulatory frameworks that effectively balance consumer protection, innovation enablement, and market competitiveness within the TMHSC sectors.